MORPHO-FUNCTIONAL CHANGES IN THE ENDOCRINE PANCREAS OF WHITE RATS UNDER METABOLIC SYNDROME CONDITIONS - Ergashev S., Usmanov R., Niyozov N. (Central Asian Journal of Medicine, 2025)
To assess the morphological characteristics of the pancreas in experimental metabolic syndrome. Materials and Methods: White laboratory rats under hypokinetic conditions were used in the experiment. To achieve the research goal, the pancreases of 51 sexually mature white laboratory rats were examined. The animals were divided into two groups. The first group consisted of intact adult rats (control). In the second group, the rats were placed in a special cage with an area of 150 square cm to induce an experimental metabolic syndrome model. Results: In experimental metabolic syndrome, vacuolization of the cytoplasm, irregular nuclear shape, and nucleolar segmentation were observed in the beta-cells of the endocrine part of the pancreas. These changes may be associated with impaired intracellular transport and reduced secretory activity. In alpha-cells located at the periphery of the islets, increased glucagon expression, chromatin condensation, and indistinct cell boundaries were detected, indicating a disruption of hormonal balance. Conclusion: Under metabolic syndrome conditions, a decrease in the number and size of pancreatic islets, structural abnormalities in beta-cells, and mild edema and vascular changes in the surrounding connective tissue were observed. These changes were accompanied by reduced hormonal activity of the gland.